The comparison of long-term oncological outcomes and complications after proximal gastrectomy with double tract reconstruction versus total gastrectomy for proximal gastric cancer - Keming Ying; Weisong Bai; Guiru Yan; Ziseng Xu; Shenheng Du; Chengxue Dang (World Journal of Surgical Oncology, 2023)
Abstract Background Conventional methods for treating patients with proximal gastric cancer (PGC) include proximal gastrectomy (PG) and total gastrectomy (TG) and such methods have become challenging due to double tract reconstruction (DTR). However, the clinical outcomes remain unclear. This study was performed with the aim of verifying that PG-DTR was beneficial in terms of reducing the incidence of postoperative complications and improving the prognosis. Methods The PGC patient cohort was retrospectively grouped into the PG-DTR and TG groups. Clinicopathological features, complications, and survival data were compared between the two groups. Results A total of 388 patients were included in the analyses. Patients who were subjected to TG tended to have more severe gastroesophageal reflux (GR) (P = 0.041), anemia (P = 0.007), and hypoalbuminemia (P < 0.001). Overall survival rates, regardless of clinical stage, were significantly different between the PG-DTR and TG groups (all P < 0.05). The multivariate Cox regression analysis confirmed that surgical procedure, tumor size, infiltration depth, lymph node metastasis, differentiation, and age were independent risk factors. The patients were likely to benefit from PG-DTR (all HR > 1 and P < 0.05). However, no significant differences were observed in the risks of GR, anemia, and hypoalbuminemia (all P > 0.05). Moreover, the nomogram derived from significant parameters showed great calibration and discrimination ability and significant clinical benefit. Conclusions The patients who underwent PG-DTR had a favorable prognosis. The risk of postoperative complications, such as severe GR, anemia, and hypoalbuminemia, was lower in PG-DTR than in TG. Thus, PG-DTR is more beneficial for patients with PGC and may be a valuable and promising surgical procedure.